Tumor Microenvironment Autophagic Processes and Cachexia: The Missing Link? - Gonçalves, Renata de Castro; Freire, Paula Paccielli; Coletti, Dario; Seelaender, Marilia (Frontiers in Oncology, 2021)
Cachexia is characterized as a syndrome that affects the entire organism, showing a variable plethora of symptoms in patients, but consistently associated with continuous and involuntary degradation of skeletal muscle mass and function loss. In cancer, this syndrome occurs in 50% of all patients, and the prevalence increases up to 80% as the disease worsens, reducing tolerance to treatment, therapeutic response, quality of life, as well as survival. An important feature of cachexia is chronic systemic inflammation and, paradoxically, immunosuppression. The interaction between tumor and peripheral tissues, with significant involvement of infiltrating immune cells in many organs and in the tumor itself, contributes to fueling systemic inflammation in cachexia. Autophagy, as a process responsible for regulating cellular metabolism and homeostasis, can interfere in metabolic profile in the tumor microenvironment. In the case of a balanced autophagy in the tumor microenvironment, infiltrating immune cells control cytokine production and secretion. On the other hand, autophagy unbalanced or dysfunctional in the tumor microenvironment impairs the control of immune cells inflammatory phenotype which upregulate metabolic consumption and cytokine production not only in the tumor microenvironment but also systemic levels in the host. We herein propose that cachexia-related chronic inflammation can be at least partly associated with the failure of autophagic processes in cancer cells. Autophagy endangers tumor cell viability by producing immunogenic tumor antigens, thus eliciting the immune response necessary to counteract tumor progression, at the same time preventing the establishment of inflammation, a hallmark of cachexia. Comprehensive understanding of this complex functional dichotomy may enhance cancer treatment response and prevent/mitigate cancer cachexia. This review summarizes the recent available literature regarding the role of autophagy within the tumor microenvironment and the consequences eliciting the development of cancer cachexia.